Analisis Proses Pengadaan Material dengan Pendekatan Simulasi di Perusahaan Listrik Negara (PLN) - Muhammad Ali; Christopher Davito Prabandewa Hertadi; Happy Aprillia; Muqimuddin Muqimuddin (Universitas Islam Raden Rahmat, Malang, 2024)
In the material procurement process, there are often delays in the arrival of materials that cause maintenance and operational delays. Evaluation of the material procurement process is necessary to identify the factors that cause delays. Utility and waiting time for various staff showed significant variations, with the highest waiting time at the approving stage (4-24 hours) and the creation of TOR, FPB, RAB documents (1-11 hours). Utilization at the FPB, TOR, RAB creation staff from 13% to 62%, RO staff 6%-55%, HPE staff 50%-77%, RKS staff 10%-52%, approving user team, assistant manager to manager of 73%-90%, PDP staff 0%-45%, HPS staff 0%-45%, PPP staff 0%-44%, entry staff 61%-81%, eval staff 4%-41%, BA staff 0-56%, PO staff 8-52%. Three improvement scenarios were developed, with scenarios 2 and 3 being the best, scenario 2 reducing resources and scenario 3 increasing the purchase of certain materials, in order to optimize inventory.